Encapsulação de β-galactosidase em co-polímero alginato-pectina e hidrólise de soro de leite e leite integral - Paiva, Maykon Jhuly Martins de (Universidade Federal do Tocantins, 2020)
The aim of this work was to investigate the immobilization of the commercial Aspergillus oryzae β-galactosidase enzyme (Deslac®) under different conditions, as well as to characterize the free and immobilized enzyme using its application in lactose hydrolysis. The experiments were conducted to identify the best yield of immobilization in calcium alginate and the use of different adjuvants. The free and immobilized enzyme were characterized as to their biochemical properties, to identify the optimum pH and temperature conditions for the lactose hydrolysis reaction, the effect of salts on the enzymatic activity and enzyme storage stability. Enzymes were analyzed to moisturize whey and whole milk. Immobilization of the enzyme β-galactosidase yields better derivative inalginate (2% w/v), glutaraldehyde(25% v/v) crosslinked pectin (2% w/v). The optimal pH to hydrolysis lactose using a soluble and immobilized enzyme was 5.0 and 6.5, respectively, and the optimum temperature was 45 °C and 40 °C, respectively. The use of magnesium sulfate and manganese sulfate influenced enzymatic activity by 195% and 150%, respectively, for an immobilized enzyme. The immobilized enzyme showed 60% stability after 10 days of storage. The immobilization process with sodium alginate + pectin and glutaraldehyde reduced diffuse effects compared to conventional alginate. The reduction of the temperature optimal activity allows a more energy-efficient process.